A Sino-U.S. comparison on workplace flexibility: evidence from multinational firms. Issue 3 (4th February 2022) - Lai, Lei; Besen, Elyssa; Sarkisian, Natalia; Xu, Qingwen
Abstract: This paper examines cross-national differences in workplace flexibility between the U.S. and China. Data from 2, 688 employees of three multinational corporations with worksites located in both the U.S. and China demonstrated that Chinese viewed workplace flexibility as less important, perceived fewer benefits and more costs associated with its use, and reported less access to and use of flexibility than Americans. Access to flexibility was linked to higher job satisfaction for Americans, but not for Chinese. Both access to and use of flexibility were linked to higher satisfaction with work-family balance for Americans, but not for Chinese, with the exception of access to flexplace that was linked to higher satisfaction with work-family balance for both. We conclude that workplace flexibility policies may produce different results in countries with different levels of industrialization (developed vs. emerging) and cultural orientation (individualism-collectivism) and suggest that such policies should be customized to improve their congruence with national contexts.